Experimental study on flexural mechanical properties of steel fiber reinforced alkali-activated slag concrete beams - Yuan, Xiaohui; Huo, Ruijin; Zhang, Xin (Frontiers in Physics, 2024)
As an environmentally friendly alternative to ordinary concrete, slag concrete is subject to limitations such as drying shrinkage and micro-cracking during its promotion and application. In order to address these challenges, steel fibers, known for their excellent tensile, shear, crackresistance, and toughness properties, have been introduced to enhance the ductility of alkali-activated slag concrete.This study utilized steel fiber content as a variable and produced eight steel fiberreinforced alkali-activated slag concrete beams to investigate their flexural mechanical properties. By exploring the influence of steel fiber content variation on the mechanical behavior of alkali-activated slag concrete beams and conducting validation through finite element analysis, the study unveiled the impact of steel fibers on the performance of alkali-activated slag concrete beams.The research findings demonstrate a significant enhancement in the flexural mechanical properties of alkaliactivated slag concrete beams with the addition of steel fibers, leading to a reduction in surface cracking and an improvement in the durability of the elements. The outcomes of this study hold crucial theoretical implications for the widespread application of steel fiber-reinforced alkaliactivated slag concrete.